Morphological Analysis of US Treated PANC-1 Spheroids - Martina Ricci; Mattia Dimitri; Martina Serio; Andrea Corvi (Applied Sciences)
This study investigates the impact of low-intensity continuous ultrasound (LICU) on pancreatic adenocarcinoma (PANC-1) spheroids, emphasizing morphological and volumetric transformations. PANC-1 spheroids were cultured and treated with LICU across frequencies from 1 to 5 MHz. Cell viability and mortality were analyzed through Calcein AM/PI staining, while volumetric and morphological changes were quantified across frequencies from 2 to 4 MHz using advanced imaging techniques and computational tools, including a custom Python OpenCv Library, AnaSP 3.0, a MATLAB based open source tool. Notably, a frequency of 3.5 MHz yielded optimal outcomes, also achieving a reduction in spheroid volume and mortality while minimizing disgregation, a factor linked to metastasis risk. These findings underscore LICU’s potential as an effective therapeutic strategy, balancing tumor reduction with the preservation of structural cohesion. The study establishes a methodological framework for optimizing LICU parameters, presenting a less invasive avenue for improving therapeutic outcomes in pancreatic cancer treatment.